1969
DOI: 10.1083/jcb.40.2.529
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Granules From Rabbit Heterophil Leukocytes Into Distinct Populations by Zonal Sedimentation

Abstract: Postnuclear supernates from homogenates of essentially pure rabbit heterophil leukocytes were fractionated by means of zonal differential centrifugation through a discontinuous sucrose gradient at various speeds. Three distinct groups of granules were characterized biochemically and morphologically. They were, in order of decreasing sedimentation coefficient: (a) Large, relatively dense granules, identified morphologically as the azurophil or primary granules, and containing essentially all of the myeloperoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
2
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(148 citation statements)
references
References 27 publications
13
132
2
1
Order By: Relevance
“…All of our findings are consistent with the view that particle uptake and granule interaction with the PV are 2 A similar distribution of enzyme activities was noted among fractions of granules separated from rabbit PMN (23,24). An acid phosphatase which was associated with slowly sedimenting particles from the rabbit cells, however, hydrolyzed p-nitrophenyl phosphate much more readily than it did 8-glycerophosphate, whereas the enzyme from guinea pig cells exhibited little preference (15).…”
Section: Discussionsupporting
confidence: 79%
“…All of our findings are consistent with the view that particle uptake and granule interaction with the PV are 2 A similar distribution of enzyme activities was noted among fractions of granules separated from rabbit PMN (23,24). An acid phosphatase which was associated with slowly sedimenting particles from the rabbit cells, however, hydrolyzed p-nitrophenyl phosphate much more readily than it did 8-glycerophosphate, whereas the enzyme from guinea pig cells exhibited little preference (15).…”
Section: Discussionsupporting
confidence: 79%
“…Biochemical and morphological studies of granulocytes from several species have revealed two types of cytoplasmic granules, namely, peroxidase-positive (azurophil or primary granules) and peroxidase-negative (specific or secondary granules) (30)(31)(32)(33). The cationic proteins of rabbit polymorphonuclear leukocytes are associated with the peroxidase-containing granules (32).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were homogenized, and a postnuclear (4,000 g-rain) supernate was prepared as described previously (3). Granules were obtained by fractionating 2.5-ml aliquots of the postnuclear supernates through discontinuous sucrose gradients consisting of three layers (8.0, 5.5, and 4.0 ml) with densities 1.08, I.…”
Section: Cell Fractionationmentioning
confidence: 99%
“…The two types of granules arise from opposite faces of the Golgi apparatus (i) during successive stages of PMN maturation (1,2). The azurophils contain myeloperoxidase, lysozyme, and a wide variety of lysosomal hydrolases, while the specifics contain alkaline phosphatase, iysozyme, and lactoferrin, but are devoid of lysosomal hydrolases (3)(4)(5).…”
mentioning
confidence: 99%